2014
DOI: 10.15288/jsad.2014.75.74
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis Use Behaviors and Social Anxiety: The Roles of Perceived Descriptive and Injunctive Social Norms

Abstract: ABSTRACT. Objective: Individuals with greater social anxiety are particularly vulnerable to cannabis-related impairment. Descriptive norms (beliefs about others' use) and injunctive norms (beliefs regarding others' approval of risky use) may be particularly relevant to cannabis-related behaviors among socially anxious persons if they use cannabis for fear of evaluation for deviating from what they believe to be normative behaviors. Yet, little research has examined the impact of these social norms on the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 61 publications
(87 reference statements)
10
39
0
Order By: Relevance
“…First, the current study replicated a growing body of work that has found greater social anxiety to be related to greater cannabis-related impairment (e.g., Agosti et al, 2002; Buckner, Heimberg, et al, 2012; Buckner et al, 2008; Stinson et al, 2006), despite not being related to greater typical cannabis use (e.g., Buckner et al, 2007; Ecker & Buckner, 2014; Ecker et al, 2014). The current study extended that work by finding that tendency to engage in PEP was positively associated with cannabis-related problem severity, but not cannabis use frequency, and that PEP mediated the relationship between social anxiety and cannabis-related problem severity.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…First, the current study replicated a growing body of work that has found greater social anxiety to be related to greater cannabis-related impairment (e.g., Agosti et al, 2002; Buckner, Heimberg, et al, 2012; Buckner et al, 2008; Stinson et al, 2006), despite not being related to greater typical cannabis use (e.g., Buckner et al, 2007; Ecker & Buckner, 2014; Ecker et al, 2014). The current study extended that work by finding that tendency to engage in PEP was positively associated with cannabis-related problem severity, but not cannabis use frequency, and that PEP mediated the relationship between social anxiety and cannabis-related problem severity.…”
Section: Discussionsupporting
confidence: 77%
“…The SIAS has demonstrated construct and discriminant validity (Mattick & Clarke, 1998), as well as test-retest reliability across clinical, community, and student samples (Mattick & Clarke, 1998; Osman, Gutierrez, Barrios, Kopper, & Chiros, 1998). It has also demonstrated good internal consistency among undergraduate cannabis users (e.g., Ecker & Buckner, 2014) and in the current study (α = 0.89).…”
Section: Methodssupporting
confidence: 60%
See 2 more Smart Citations
“…Our findings add to a growing body of work indicating that individuals with social anxiety experience more cannabis-related problems (e.g., Buckner, Heimberg, et al, 2012; Ecker & Buckner, 2014). The current study extended this work by determining that among those who believe their friend experiences more problems, those with greater social anxiety endorsed the most cannabis-related problems.…”
Section: Discussionsupporting
confidence: 69%